Using the Community-Based Health Planning and Services Program to Promote Skilled Delivery in Rural Ghana : Socio-Demographic Factors that Influence Women Utilization of Skilled Attendants at Birth in Northern Ghana - Sakeah, Evelyn; Doctor, Henry V.; McCloskey, Lois; Bernstein, Judith; Yeboah-Antwi, Kojo; Mills, Samuel (BioMed Central, 2015)
The burden of maternal mortality in sub-Saharan Africa is enormous. In Ghana the maternal mortality ratio was 350 per 100,000 live births in 2010. Skilled birth attendance has been shown to reduce maternal deaths and disabilities, yet in 2010 only 68% of mothers in Ghana gave birth with skilled birth attendants. In 2005, the Ghana Health Service piloted an enhancement of its Community-Based Health Planning and Services (CHPS) program, training Community Health Officers (CHOs) as midwives, to address the gap in skilled attendance in rural Upper East Region (UER). The study determined the extent to which CHO-midwives skilled delivery program achieved its desired outcomes in UER among birthing women.